2018
DOI: 10.5455/aim.2018.26.115-118
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer-based Tests on Nursing Students' Test Anxiety: a Quasi-experimental Study

Abstract: Background:Test anxiety often leads to poor academic performance. This study aimed to determine the effect of computer-based tests on nursing students’ test anxiety.Methods:This quasi-experimental study was conducted in 2016 on 39 nursing student with anxiety score under 128 on Spielberger’s State-Trait Inventory (STAI). They were randomly allocated to computer-based tests (CBT) and paper-based test (PBT) group. Prior to exam, all students completed Sarason’s Test Anxiety Scale (TAS). We administered CBT for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
3
11
2
Order By: Relevance
“…At the same time, another half also agreed with the item and was found to have a varying percentage of mild, moderate, or even severe stress. This is consistent with the results of studies 18 , 32 , 33 reporting high test anxiety among students whereas another study 21 reported medium test anxiety. This variation in the degree of test anxiety may relate to the complexity of certain topics, different items designed by different staff, and also the interest in the topic.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, another half also agreed with the item and was found to have a varying percentage of mild, moderate, or even severe stress. This is consistent with the results of studies 18 , 32 , 33 reporting high test anxiety among students whereas another study 21 reported medium test anxiety. This variation in the degree of test anxiety may relate to the complexity of certain topics, different items designed by different staff, and also the interest in the topic.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the cognitive mechanism V, the data indicated that the students considered the test mode followed by the exam type as the most relevant factors. These findings do not align with the results reported by Deloatch et al (2016) and Kolagari et al (2018) who found non-significant differences in the test anxiety levels produced by different test modes. Kolagari et al (2018) nonetheless noted that the students showed greater anxiety in computerized exams.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings do not align with the results reported by Deloatch et al (2016) and Kolagari et al (2018) who found non-significant differences in the test anxiety levels produced by different test modes. Kolagari et al (2018) nonetheless noted that the students showed greater anxiety in computerized exams. This finding is countered by the results obtained in this study, as students anticipated much greater anxiety levels when presented by face-to-face tests (whether paper or computerized) compared to those in the distance mode (online computerized test).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study found that the anxiety score of the nursing students undertaking CBT was higher than those who took paper-based test (PBT) [11]. Although the score was not statistically significantly different, the higher anxiety score among CBT test taker should be anticipated.…”
Section: Results and Analysismentioning
confidence: 85%